Arthritogenic alphaviruses: new insights into arthritis and bone pathology. Issue 1 (January 2015) - Chen, Weiqiang; Foo, Suan-Sin; Sims, Natalie A.; Herrero, Lara J.; Walsh, Nicole C.; Mahalingam, Suresh
Highlights: Enhanced osteoclastogenesis and bone loss take place during arthritogenic alphavirus infection. There is strong interplay between immune responses in alphaviral arthritis and bone health. There is a potential risk of alphavirus infection exacerbating underlying inflammatory arthritis. Targeting osteotropic factors may be efficacious in treating alphaviral-induced bone loss. Abstract : Arthritogenic alphaviral infection begins as a febrile illness and often progresses to joint pain and rheumatic symptoms that are described as polyarthritis. Alphaviral arthritis and classical arthritides share many similar cellular and immune mediators involved in their pathogenesis. Recent in vitro and in vivo evidence suggests that bone loss resulting from increased expression of bone resorption mediators may accompany alphaviral infection. In addition, several longitudinal studies have reported more severe and delayed recovery of alphaviral disease in patients with pre-existing arthritic conditions. This review aims to provide insights into alphavirus-induced bone loss and focuses on aspects of disease exacerbation in patients with underlying arthritis and on possible therapeutic targets.